Hierarchical structure of hollow thorn-like polypyrrole microtubes with enhanced electrochemical performance. Issue 2 (2nd December 2014) - Li, Mei; Yang, Lanlan; Zhang, Yunqiang
Abstract : The hydrophilic sulfonate groups of SDBS were negatively charged, and were absorbed by the cationic pyrrole radicals produced during polymerization to PPy. The electrostatic absorption between the oppositely charged ions induced so-called thorns. Abstract : A hollow thorn-like polypyrrole (PPy) microtube structure (HTPMT) has been prepared by in situ chemical oxidation polymerization using Methyl Orange (MO) and sodium dodecylbenzene sulfonate (SDBS) as double soft templates, in which the MO and SDBS performed both as surfactant and dopant. The hierarchical structure of HTPMT formed in the presence of MO and SDBS was different from that of polypyrrole microtubes (PMT) or nanoparticles (PNP) using MO and SDBS separately. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images showed that the morphology of the HTPMT had the appearance of thorns growing on the surface of the PMT. The TEM images of the MO and SDBS solutions revealed that PPy had polymerized on the surface of the end-closed MO tubes and in the vesicular SDBS micelles. Electrostatic attraction between the anionic SDBS micelles and cationic pyrrole radicals during the polymerization assisted the formation of the HTPMT. The HTPMT exhibited improved electrochemical performance and thermal stability compared with PMT or PNP, illustrating that the morphology and structure of the conductive polymer influenced the electrochemical performance of the electrode materials.